Mengkaji Peran Komite Ekonomi Kreatif dan Unsur Pemerintah Dalam Pengembangan Sektor Ekonomi Kreatif di Kabupaten Grobogan, Menghadapi Era Ekonomi Digital - Winarsih; Sri Martono (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background: The phenomenon of shifting waves of economic orientation, starting from the agricultural economy, moving to industrialization and then the era of the information economy has an impact on competitiveness emergency and increasingly tight market competition. Many countries are starting to realize that the industrial sector is no longer the main economic resource, but rather creative human resources, which is marked by the emergence of a new economic era that prioritizes information and creativity, which is known as the creative economy. Purpose: The aim of the research to make a contribute to the Grobogan Regency Creative Economy Committee to formulate appropriate strategies as a basis for carrying out its role as a driving force through coaching and mentoring creative economy actors in Grobogan Regency, especially in increasing readiness to face the demands of global competition in the era of economic digitalization which requires actors The creative economy is technologically literate or able to follow developments in science and technology. Methods: This study employs descriptive Qualitative method. Conclusion: The employment of marketing principals is greatly significant in facing the global competition through creative economy products penetration. The strategy in product designs, targeting, product differentiation, and marketing strategy is a crucial in improving the product competitive advantage. In order to recognize the competitors’ strengths and market tastes, marketing intelligence is required. In this case, the competition in globalization era is the economic competition and the main tool required is creative economy. Due to the tight commitment from the creative economy stakeholders in Indonesia in applying the creative economy momentum, creative economy becomes the spearhead the new economic growth in increasing the nation prosperity which leads to ‘Indonesia Emas 2045’. Suggestion: The synergy of the whole stakeholders is required to overcome the barriers and treats in creative economy development. The central and local government who formulate the policy is expected to fully commit to facilitate, inspire, and motivate the creative economy development through measurable actions based on priority scale, focus, and concrete